Exploration of Consumer Buying Interests at Tiktok Stores Live Streaming Based on the Stimulus Organism Response (SOR) Framework - Dinanti, Windy Dara; Bharata, Wira (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2023)
Technological developments are currently increasing rapidly so that entrepreneurs advance their business ventures with various innovations. No wonder there are many emerging marketplaces that provide several conveniences in shopping. The TikTok application is one of the most popular marketplaces. This study aims to determine the effect of Store Atmosphere, Online Customer Reviews and Online Customer Ratings on Purchase Intention with Trust as a mediating variable at the TikTok Shop. This study uses quantitative data and this type of research is associative research. The population used in this research is live streaming viewers @oktaviana_tas_grosir. The sample collection technique uses a non-probability sampling technique. The sample in this study was determined by 100 respondents. The data analysis technique in this study used the Smart PLS version 3.0 tool. The results of this study indicate that Store Atmosphere, Online Customer Reviews and Online Customer Ratings have a positive effect on Trust. Online Customer Reviews and Online Customer Ratings have a positive effect on Purchase Intention, while the Store Atmosphere has a negative effect on Purchase Intention. Trust has a positive effect on Purchase Intention. Trust is able to mediate Store Atmosphere, Online Customer Reviews and Online Customer Ratings on Purchase Intention positively.